Późne arcydzieła Miłosza - Kuczera-Chachulska, Bernadetta (Colloquia Litteraria, 2011)
In the last lyric Czesław Miłosz raises the themes somehow similar to those which appear in Mickiewicz’s Lozanne lyric: their characteristic feature is also the similarity between the attitudes and formal solutions. The aesthetic category of the “Lozanne issue” to a great extent builds an extremely brave shape of Miłosz’s late lyric.